Los personajes en la novela Dios no quiere pobres - Pumalaza Díaz, Alberto Lázaro (2019)
The present study aims to reflect on the characters of the novel God does not want poor people. They are fictional characters that are present in our poetry. The challenge is to look with critical eyes, our narrative. Likewise, the suffering, indifference, injustice and corruption in which the characters are involved are identified. It is a study where we deal with the discussion of narrative, fiction and how to create characters.